2012
DOI: 10.1017/s1751731112001012
|View full text |Cite
|
Sign up to set email alerts
|

Administration of distillate thyme leaves into the diet of Segureña ewes: effect on lamb meat quality

Abstract: The effect of including thyme by-products from the distillation industry into the diet of pregnant ewes on the final quality of lamb meat was evaluated during meat storage in modified atmosphere. A total of 36 Segureña ewes were randomly assigned to three homogeneous groups. One group was fed a basal diet (BD) as control (C), whereas the diet of the other two groups was modified by substituting 10% (T1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
5
30
0
Order By: Relevance
“…After this study, it was reported that both distilled leaves (rosemary and thyme) were readily accessible source of natural antioxidants in animal feedstuffs, these by-products were added to the feed of pregnant ewes [67][68][69][70][71]. As shown previously with the liposomes model system study, the meat of lambs from ewes fed with distilled rosemary and thyme leaf had lower levels of lipid oxidation and these additives were considered a good alternative to using synthetic antioxidant in animal diets.…”
Section: Liposomesmentioning
confidence: 65%
“…After this study, it was reported that both distilled leaves (rosemary and thyme) were readily accessible source of natural antioxidants in animal feedstuffs, these by-products were added to the feed of pregnant ewes [67][68][69][70][71]. As shown previously with the liposomes model system study, the meat of lambs from ewes fed with distilled rosemary and thyme leaf had lower levels of lipid oxidation and these additives were considered a good alternative to using synthetic antioxidant in animal diets.…”
Section: Liposomesmentioning
confidence: 65%
“…One possible strategy that may be suitable for use with VP or MAP is to include phytochemicals in the diet of animals to preserve the resulting meat. Indeed, several diets based on plant phenolic compounds have been used in recent years to improve lamb meat preservation (Luciano et al ; Jerónimo et al ; Nieto et al ; Rivas‐Cañedo et al ; Inserra et al ), in particular, rosemary and/or its products (Nieto et al ; Bañón et al ; Morán et al , ; Smeti et al ; Vasta et al ; Ortuño et al , ; Serrano et al ). Among the products tested in lambs, a dietary rosemary extract (RE) containing carnosic acid and carnosol has been seen to lead to the deposition in muscle of a diterpenic metabolite derived from the carnosol with antioxidant and antimicrobial potential effects (Jordán et al ).…”
Section: Introductionmentioning
confidence: 99%
“…One possible strategy that may be suitable for use with VP or MAP is to include phytochemicals in the diet of animals to preserve the resulting meat. Indeed, several diets based on plant phenolic compounds have been used in recent years to improve lamb meat preservation (Luciano et al 2009;Jerónimo et al 2012;Nieto et al 2012;Rivas-Cañedo et al 2013;Inserra et al 2014), in particular, rosemary and/or its products (Nieto et al from the carnosol with antioxidant and antimicrobial potential effects . Other studies suggest that the antimicrobial potential of RE would not be well used when lamb fillets are packed under a bacteriostatic atmosphere Serrano et al 2014;Ortuño et al 2015), hence the interest in knowing whether RE is able to delay microbial spoilage in meat products that present a high microbial risk, such as raw patties made from frozen-thawed pieces (Khalafalla et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…R. officinalis is resistant to dehydrated stress and can continue to grow under drought conditions [19]. Various studies have reported the effects of R. officinalis plants on food preservation from oxidation and microbial contamination [20][21][22]. In traditional medicine, this plant is used for anti-asthma effects, food digestion, sedative, headache, circulatory disorders, that increased visual acuity, anti-rheumatism and memory stimulus [23][24].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%